3-{(E)-[1-(2-Hydroxyphenyl)ethylidene]-amino}-1-(2-methylphenyl)thiourea - Abdus, Salam; Md. Abu, Affan; Mohd Razip, Asaruddin; Tiekink, Edward (IUCR, 2011)
In the title thiourea derivative, C16H17N3OS, the hydroxy-and methyl-substituted benzene rings form dihedral angles of 9.62 (12) and 55.69 (6)degrees, respectively, with the central CN3S chromophore (r.m.s. deviation = 0.0117 angstrom). An intramolecular O-H center dot center dot center dot N hydrogen bond ensures the coplanarity of the central atoms. The H atoms of the NH groups are syn and the conformation about the N = C double bond [1.295 (4) angstrom] is E. In the crystal, helical supramolecular chains sustained primarily by N-H center dot center dot center dot S hydrogen bonds are found. Additional stabilization is provided by C-H center dot center dot center dot pi and pi-pi [ring centroid(hydroxybenzene)center dot center dot center dot ring centroid(methylbenzene) = 3.8524 (18) angstrom] interactions.